1993
DOI: 10.1159/000227206
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Clinical and Histologic Outcome of Intraperitoneal Hyperthermic Perfusion for Patients with Gastric Cancer and Peritoneal Metastasis

Abstract: In 15 patients with refractory gastric cancer and peritoneal metastasis, the relationship among histologic outcome of intraperitoneal hyperthermic perfusion (IPHP), extent of peritoneal metastasis, and cause of death was studied. The IPHP treatment did not kill all the gastric cancer cells which had penetrated deeply into subperitoneal layers. In contrast, gastric cancer cells in the abdominal effusion and/or lavage vanished. Three patients with peritoneal metastasis, deeply invaded and spread all over the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…The largest experience published so far was a retrospective French study involving 159 patients which confirmed this combination advantage in a selected CCR0 group of patients[35]. The dismal effect of HIPEC in patients with extensive peritoneal carcinomatosis not amenable to downstaging to CCR-0 may be explained by limited drug penetration leading to no anti-tumor effect on the deeply invasive microfoci[38]. Thus, drug delivery system with high permeability has the potential perspective role in the treatment of extensive peritoneal carcinomatosis cases[39].…”
Section: Effective Treatments For Patients With Peritoneal Metastasismentioning
confidence: 99%
“…The largest experience published so far was a retrospective French study involving 159 patients which confirmed this combination advantage in a selected CCR0 group of patients[35]. The dismal effect of HIPEC in patients with extensive peritoneal carcinomatosis not amenable to downstaging to CCR-0 may be explained by limited drug penetration leading to no anti-tumor effect on the deeply invasive microfoci[38]. Thus, drug delivery system with high permeability has the potential perspective role in the treatment of extensive peritoneal carcinomatosis cases[39].…”
Section: Effective Treatments For Patients With Peritoneal Metastasismentioning
confidence: 99%
“…For that reason, various clinical attempts have been made to treat the peritoneal dissemination of gastric cancer, including systemic chemotherapy [2], intraperitoneal chemotherapy and/or hyperthermia [3], and aggressive surgery [4]. However, the results of these therapies have been unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…The distance that drugs directly penetrate is only a few millimeters [18, 21], which can be interpreted to mean that there is no direct effect of drugs on any macroscopic residual tumors in the peritoneal cavity. For serosal invasion or peritoneal metastasis, several trials of combined IPT and hyperthermic perfusion have been conducted [24, 25, 26], and, at least in part, positive effects on patient survival have been reported. More recently, Crookes et al [27]achieved a median survival of over 4 years after combined preoperative systemic chemotherapy with postoperative IPT.…”
Section: Discussionmentioning
confidence: 99%